Carbohydrate allocation strategies and C/N balance shape root plasticity of urban tree species under ozone stress - Jingwen Fu; Yaowu Tu; Di-Ao Yan; Xinxin Hao; Xizi Wang; Shuangjiang Li; Feiyun Xu; Xiangyang Yuan; Zhaozhong Feng; Shenglan Li (Journal of Environmental Sciences, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Pectin film reinforced with self-assembled lignin/bayberry bark tannin nanoparticles for preserving perishable fruits - Haonan Guo; Yijing Li; Xinxin Cheng; Quanbin Fu; Jin Wang; Bowen Zhang; Shikai Zhang; Houshen Li (Food Hydrocolloids, 2026)

Corrigendum to “Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning” [Environ Res. 306 (2026) 125271] - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

Spatiotemporal heterogeneity in the association between surface ozone and wheat yield across China: A phenological analysis - Tianning Zhang; Yuanyuan Li; Xinxin Li; Rui Wang; Kaiyue Wei; Haijiang Kong; Huan Liu; Hongquan Song; Yongze Song; Shenglei Fu (European Journal of Agronomy, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Kinetic Modelling of the Decay of Respiratory Syncytial Viruses (RSV) Facilitated a Robust Wastewater-Based Surveillance for RSV - Yuqing Long; Jiayi Liu; Xiuyuan Shi; Xueling Yang; Yongyan Long; Jinzhou Xiao; Xinxin Han; Songzhe Fu (Food and Environmental Virology, 2026)

Source-oriented probabilistic human health risk assessments and priority heavy metal pollution control areas identification in the Laoguan river basin - Xinxin Long; Changyv Zhou; Hui Fu; Shaokang Meng; Yuan Wei (Environmental Pollution, 2026)

SlMYB2: an R2R3-MYB transcription factor enhancing drought, salt, and cadmium tolerance in Solanum lycopersicum - Shan Fu; Fei Liu; Ying Li; Chunyan Lu; Tiantian Liu; Songzhou Tian; Wei Jin; Pingan Guo; Liang Chen; Xinxin Geng (Plant Cell Reports, 2026)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Metabolic fate of polyphenols in LAB-fermented kiwifruit juice: A comparative study of single and mixed cultures with targeted metabolomics and enzymatic evidence - Heng Liu; Weichong Fu; Xinyue Lian; Chengwei Pu; Xinxin Wu; Jingming Li (Food Chemistry, 2025)

ViruSeg: Harnessing the Power of Large Language-Image Model for Enhanced Virus Image Segmentation - Shengxiang Wang; Xiangzheng Fu; Zhenya Du; Xinxin Liu; Qiaochu Mai; Linlin Zhuo; Boqia Xie; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Fluorescent Probe for Recognizing Fe3+ in Aqueous Solutions and its Applications - Shengling Li; Xiangpeng Kong; Qi Wang; Jinghua Fang; Chenwei Fu; Xinxin Zhang; Jiahui Jia; Yikai Chen (Journal of Fluorescence, 2025)

Integrating process-based modeling with genetic algorithm to optimize wastewater treatment plant operations incorporating greenhouse gas emissions - Xuyang Wu; Jian He; Guangtao Fu; Zheng Zheng; Xinxin Zheng; Xiaogang Li; Xiaoying Yang (Process Safety and Environmental Protection, 2025)

The combination of linkage mapping, genome-wide association study, and dynamic transcriptome analysis reveals conserved candidate genes for salt tolerance in maize - Ziyi Xiao; Zhenyuan Pan; Xinxin Liu; Xueqing Zheng; Guantao Wang; Yayu Fu; Mengmeng Li; Bin Hou; Xuhua Li; Ming Zhang; Chunlan Jia; Fazhan Qiu (Theoretical and Applied Genetics, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

Low-hysteresis, high-fidelity flexible strain sensor with interconnected conductive network design for harsh environments and manipulator control - Peng Ding; Jia Wang; Zhitao Xiao; Xinxin Zhao; Yi Zhao; Xiaofei Fu; Wei Zhai; Kangkang Zhou; Kun Dai; Guoqiang Zheng; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2025)

Microbial Life History Mediates the Drought‐Induced Decrease in Wood Decomposition in Subtropical Forests - Shuxian Jia; Xuhui Zhou; Yuling Fu; Guiyao Zhou; Lingyan Zhou; Xinxin Wang; Zheng Jiang; Jordi Sardans; Josep Penuelas (Ecology Letters, 2025)
Progressive intensification of drought regimes worldwide threatens wood decomposition ‐ a critical biogeochemical process in forest carbon cycling. However, the interactions between microbial strategies, wood traits and microclimate in regulating wood decomposition remain poorly understood under drought conditions. In a throughfall exclusion experiment (control 35% and 70% rainfall reduction) across 12 tree species, we found that drought‐induced reductions in wood CO 2 efflux rates were primarily driven by wood traits (density and carbon reduction) and shifts in fungal K / r ‐strategies. Coarse wood debris with higher Basidiomycota and lower Ascomycota abundance decomposed faster. Significant positive correlations were observed between fungal K / r ‐strategies and wood CO 2 efflux under control, 35%, and 70% rainfall reduction, while bacterial strategies showed no correlation. Our findings highlight the greater drought sensitivity of fungi than bacteria, emphasising their critical role in forest carbon dynamics and informing carbon models to improve the prediction of climate‐biosphere feedback in the changing world.

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

UV-aging process of titanium dioxide nanoparticles aggravates enterohepatic toxicity of bis(2-ethylhexyl)-2,3,4,5-tetrabromophthalate to zebrafish - Yuxi Zhou; Kaiyu Fu; Fan Li; Yindan Zhang; Xinxin Ren; Bingjie Li; Shengmin Wu; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2025)

Precipitation versus dissolution at the phosphorus and Solanum nigrum L. root exudate interface: Implications for lead rebound in rhizosphere soils - Jingwei Zhang; Hao Shi; Yiquan Xing; Yixin Chen; Jiacheng Li; Haojie Fu; Guoqing Dai; Zhaojie Cui; Lei Wang; Xinxin Li (Science of The Total Environment, 2024)

The association of mixed multi-metal exposure with sleep duration and self-reported sleep disorder: A subgroup analysis from the National Health and Nutrition Examination Survey (NHANES) - Zifan Zhu; Yongjun Wang; Yuanlong Wang; Maoling Fu; Xinxin Luo; Guojun Wang; Jian Zhang; Xiujuan Yang; Wei Shan; Cunxue Li; Tiebang Liu (Environmental Pollution, 2024)

N-doped carbon dots/SnS2 heterostructures for ultra-fast and sub-ppb-level detection of NO2 in multiple environments - Ping Guo; Xinxin He; Xuyang An; Xingyu Zhang; Shuai Liang; Jia Zhang; Yongqing Fu (Chemical Engineering Journal, 2024)

Programmed DNA tile response system enabled accurate detection of ATP for clinical diagnosis - Dongxia Li; Yanan Peng; Liangqing Lu; Delun Chen; Bingrong Wang; Qiumei Pu; Qionglin Zhou; Xinxin Xiao; Mingpeng Fu; Xiaohong Wang; Jinchun Tu; Hua Pei; et al. (Chemical Engineering Journal, 2024)

Androgens exert multifaceted functions in sex differences analyzed through single-cell transcriptome - Xinxin Tang; Yinkun Fu; Zhihui Zou; Yue Li; Ming He (Science China Life Sciences, 2024)

TaCDPK1-5A positively regulates drought response through modulating osmotic stress responsive-associated processes in wheat (Triticum aestivum) - Xiaoyang Hou; Yongli Zhang; Xinxin Shi; Wanrong Duan; Xiaojin Fu; Jinzhi Liu; Kai Xiao (Plant Cell Reports, 2024)

Fungi and bacteria trade-off mediates drought-induced reduction in wood decomposition - Shuxian Jia; Tengfeng Yuan; Yuling Fu; Josep Penuelas; Guiyao Zhou; Lingyan Zhou; Dingqin Liu; Yanghui He; Ruiqiang Liu; Xinxin Wang; Bingqian Song; Zheng Jiang; et al. (CATENA, 2024)

Converting fruit peels into biodegradable, recyclable and antimicrobial eco-friendly bioplastics for perishable fruit preservation - Shikai Zhang; Xinxin Cheng; Wenjing Yang; Quanbin Fu; Feng Su; Peng Wu; Yijing Li; Fen Wang; Houshen Li; Shiyun Ai (Bioresource Technology, 2024)

Prediction of emission characteristics of diesel/n-hexanol/graphene oxide blended fuels based on fast outlier detection-sparrow search algorithm-bidirectional recurrent neural network - Changcheng Fu; Xinxin Cao; Lu Liang; Tiecheng Su; Wei Guan; Mingzhang Pan; Zhiqing Zhang; Hao Chen; Xiaorong Zhou (Process Safety and Environmental Protection, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Pectin-based film activated with carboxylated cellulose nanocrystals-stabilized oregano essential oil Pickering emulsion - Wenjing Yang; Shikai Zhang; Yanna Hu; Quanbin Fu; Xinxin Cheng; Yijing Li; Peng Wu; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2024)

Atomic selenium regulating endows three-dimensional N-doped carbon with fast and stable potassium ion storage - Xinxin Jia; Yang Guo; Shengyang Li; Song Chen; Wei Chen; Lei Wang; Licai Fu; Chunyu Cui; Jian Zhu; Bingan Lu (Chemical Engineering Journal, 2024)

Boron nitride-alginate coordination interactions enabling hydrogels with enhanced mechanical strength and heat resistance - Wenjing Geng; Yaohui Xu; Chan Guo; Yuchen Liu; Xinxin Ye; Qiuwen Liu; Hui Zhang; Chen Fu; Fengguang Liu; Weiwei Lei; Liang Yuan; Cheng Chen (Carbohydrate Polymers, 2024)

Biogeochemical processes in heterogeneous soil-Solanum nigrum L. system control lead partitioning: Roles of strengite and oxalated zero-valent iron nanoparticle - Guoqing Dai; Hao Shi; Murray B. McBride; Haojie Fu; Zheng Li; Xinlei Wang; Shu Yang; Lei Wang; Fayuan Wang; Xinxin Li (Journal of Cleaner Production, 2024)

Drought-induced changes in rare microbial community promoted contribution of microbial necromass C to SOC in a subtropical forest - Xinxin Wang; Lingyan Zhou; Yuling Fu; Zheng Jiang; Shuxian Jia; Bingqian Song; Dingqin Liu; Xuhui Zhou (Soil Biology and Biochemistry, 2024)

Regional background ozone estimation for China through data fusion of observation and simulation - Zhixu Sun; Jiani Tan; Fangting Wang; Rui Li; Xinxin Zhang; Jiaqiang Liao; Yangjun Wang; Ling Huang; Kun Zhang; Joshua S. Fu; Li Li (Science of The Total Environment, 2024)

Hydrolase and plastic-degrading microbiota explain degradation of polyethylene terephthalate microplastics during high-temperature composting - Xiaoxiao Li; Xinxin Liu; Junren Zhang; Fu Chen; Muhammad Khalid; Jieqi Ye; Martin Romantschuk; Nan Hui (Bioresource Technology, 2024)

Recommendations on benchmarks for photochemical air quality model applications in China — NO2, SO2, CO and PM10 - Hehe Zhai; Ling Huang; Chris Emery; Xinxin Zhang; Yangjun Wang; Greg Yarwood; Joshua S. Fu; Li Li (Atmospheric Environment, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Tailoring graphene oxide nanofiltration membrane with adjustable nanochannels for enhanced molecule separation - Wenjing Geng; Zechen Zhang; Qi Guo; Yuchen Liu; Xinxin Ye; Hui Zhang; Chen Fu; Fengguang Liu; Yujun Zhu; Cheng Chen (Chemical Engineering Journal, 2023)

A review on distribution, biogeochemistry of antimony in water and its environmental risk - Xinxin Fu; Xianjun Xie; Laurent Charlet; Jing He (Journal of Hydrology, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

Fibrous mats based skin sensor with ultra-sensitivity and anti-overshooting dynamic stability enhanced with artificial intelligence - Hui Chen; Jian Zhou; Xinxin Long; Fengling Zhuo; Ying Liu; Yihan Zhao; Jianfei Xie; Huigao Duan; Yongqing Fu (Chemical Engineering Journal, 2023)

Condensation retardation performance of metal-organic framework-based composite humidity-control materials in a radiation cooling room - Huibo Zhang; Lin Fu; Xinxin Wang; Jiang Chang (Building and Environment, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

TMT-based quantitative proteomics analysis reveals the differential proteins between fresh and frozen-thawed sperm of yak (Bos grunniens) - Yilin Fan; Xiaowei Li; Yu Guo; Xiaoqiang He; Yanwen Wang; Dan Zhao; Yan Ma; Xinxin Feng; Jiyue Zhang; Jian Li; Xiangdong Zi; Xianrong Xiong; et al. (Theriogenology, 2023)

Novel nanozyme Ag/Fe3O4@h-BN with peroxidase-mimicking and oxidase-mimicking activities for dye degradation, As(V) removal and detection - Ziming Xin; Kaifeng Duan; Qizheng Zhuo; Qianqian He; Xiao Zhang; Chuanjun Zheng; Xiaoyu Han; Tianfang Han; Zhongtian Fu; Xinxin Xu; Xin Zhao (Chemical Engineering Journal, 2023)

PET addition delays the composting mature process and promotes microbiota associated with plastic degradation in plastisphere - Xiaoxiao Li; Xiaoyan Qi; Xinxin Liu; Muhammad Khalid; Jieqi Ye; Martin Romantschuk; Fu Chen; Yinfeng Hua; Nan Hui (Journal of Cleaner Production, 2023)

Geraniin targeting CaMKK2 inhibits lipid accumulation in 3T3-L1 adipocytes by suppressing lipogenesis - Ji Li; Xuedong Wang; Xiangyu Meng; Xin Zhou; Han Huang; Yi Feng; Yujie Fu; Xinxin Liu; Bo Yu (Chemico-Biological Interactions, 2023)

Exosomes from human urine-derived stem cells carry NRF1 to alleviate bladder fibrosis via regulating miR-301b-3p/TGFβR1 pathway - Junwei Wu; Xinxin Wang; Guoping Fu; Yiyuan Feng; Yan Wang; Guoxian Zhang; Yudong Wu; Lirong Zhang; Hongyu Meng; Jianguo Wen; Bing Zhang; Qingwei Wang (Molecular and Cellular Biochemistry, 2023)

Performance of oxalate-doped hydroxyapatite as well as relative contribution of oxalate and phosphate for aqueous lead removal - Haojie Fu; Xinxin Li; Guoqing Dai; Maojuan Bai; Wei Sheng; Xu Zhang; Juan Liu; Lei Wang (Science of The Total Environment, 2023)

Multi-Omics Study on the Molecular Mechanisms of Tetraodon Nigroviridis Resistance to Exogenous Vibrio Parahaemolyticus Infection - Shoujia Jiang; Lijun Fu; Zijian Gao; Hengwei Deng; Yong Zhang; Xinxin You; Qiong Shi; Danqi Lu (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is an important marine pathogen that causes inflammation and even death in teleost fishes. It has brought significant economic losses to the aquaculture industry as well as high risks to the sustainable development of marine fisheries. In the present study, the fish Tetraodon nigroviridis and the bacterial pathogen Vibrio parahaemolyticus were used to explore the molecular mechanisms underlying the immune response of T. nigroviridis to V. parahaemolyticus exogenous infection. The microRNA (miRNA)–mRNA–protein omics and corresponding experimental validation, followed by comparative analysis, revealed several differentially expressed genes involved in various components of the immune system, including the following: complement system, chemokines, lysosomes, phagocytes, B-cell receptor signaling pathway, T-cell receptor signaling pathway, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway, and phospholipid metabolism, among others. Especially, the complements component 3 (C3) gene and protein expression levels were significantly higher after V. parahaemolyticus infection, and miRNAs targeting C3, including mir-6089-y, mir-460-y, and mir-1584-x, were significantly down-regulated. The gene and protein expression levels of complement 1 subunit qA (C1qA) were significantly down-regulated, while mir-203 targeting C1qA was significantly up-regulated. Overall, four complement genes (C1qA, IG, C3, and C5) , which are key genes in the classical pathway of complement system activation for inflammatory response, were identified. Evolutionary analysis suggested that T. nigroviridis, acquired an increased ability to recognize pathogens by evolving a more complex complement system than terrestrial vertebrates. In addition, quantitative real-time polymerase chain reaction showed high consistency with the obtained multi-omics results, indicating the reliability of the sequencing data generated in the present study. In summary, our findings can serve as a fundamental basis for further in-depth multi-omics studies on the inflammatory processes of aquatic pathogens hindering fish sustainable production.

Assessing the impacts of natural disasters on rice production in Jiangxi, China - Xiao Fu; Guannan Zhao; Weicheng Wu; Bin Xu; Jie Li; Xiaoting Zhou; Xinxin Ke; Yuan Li; Wenjing Li; Cuimin Zhou; Jingheng Jiang; Ming Zhang; et al. (International Journal of Remote Sensing, 2022)

Bisphenol A induces ovarian cancer cell proliferation and metastasis through estrogen receptor-α pathways - Chen Sang; Yu Song; Tong-wang Jin; Shuo Zhang; Linyan Fu; Yi Zhao; Xinxin Zou; Zhe Wang; Hui Gao; Sijin Liu (Environmental Science and Pollution Research, 2021)

A New Perspective on Ameliorating Depression-Like Behaviors: Suppressing Neuroinflammation by Upregulating PGC-1α - Xinxin Fu; Jie Jiao; Tingting Qin; Jiayu Yu; Qiang Fu; Xueyang Deng; Shiping Ma; Zhanqiang Ma (Neurotoxicity Research, 2021)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

A Lipid Micellar System Loaded with Dexamethasone Palmitate Alleviates Rheumatoid Arthritis - Xinxin Wang; Yan Feng; Jijun Fu; Cuishuan Wu; Bing He; Hua Zhang; Xueqing Wang; Wenbing Dai; Yong Sun; Qiang Zhang (AAPS PharmSciTech, 2019)

Colletotrichum atractylodicola sp. nov.: the anthracnose pathogen of Atractylodes chinensis in China - Haijiao Xu; Rujun Zhou; Junfan Fu; Yue Yuan; Xinxin Ge; Ulrike Damm (Mycological Progress, 2018)

Long-term plastic film mulching and fertilization treatments changed the annual distribution of residual maize straw C in soil aggregates under field conditions: characterization by 13C tracing - Xinxin Jin; Tingting An; Aaron R. Gall; Shuangyi Li; Liangjie Sun; Jiubo Pei; Xiaodan Gao; Xuan He; Shifeng Fu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2018)

Physiological and proteomic changes in Zizania latifolia under chilling stress - Zihong Ye; Junping Liu; Ye Jin; Haifeng Cui; Xinxin An; Xianshu Fu; Xiaoping Yu (Biologia, 2017)